MALAPRAKTIK DALAM PENYELENGGARAAN PEMILIHAN UMUM KEPALA DAERAH (STUDI KASUS: PEMILIHAN GUBERNUR PROVINSI DKI JAKARTA TAHUN 2017) - Cristian Pattar Pandapotan; Fitriyah . (Journal of Politic and Government Studies, 2019)
The presence of Regional Head Elections is actually a manifestation of a people's sovereignty that has been fought since the past. In addition, the mechanism of this election is expected to be able to produce a leader who is in accordance with the will of the people based on the principles of a healthy and responsible democracy. DKI Jakarta Province itself is one of the regions in Indonesia that organizes regional elections. It is status as a state capital as well as a barometer center of the life of government and the nation's economy makes the DKI Jakarta regional election projected to be a role model for other regions in organizing a party for local democracy. Unfortunately, behind the success of the Jakarta Regional Election there were black spots which showed a lot of malpractice such as fraud, violations, and manipulation at each stage of its implementation. The results of this study indicate that there is malpractice with the aim of rigging the regulations or rules of the elections so that they can influence the results of the vote which impacts will harm certain parties. There are various types of violations occurring at all stages of the DKI Jakarta regional election in 2017. The condition of the legal framework that is still premature is believed to be the main root of all the phenomena of malpractice in the Election in Jakarta. In addition, the inaction of the election organizers in an effort to guard and eradicate any violations of the elections made the proliferation of all kinds of violations in this election. The situation was further aggravated when the community did not have enough intellectuality of politics in the face of the heat of a political contestation in Jakarta.Keywords: malpractice, local election, law enforcement